2012
DOI: 10.1016/j.brainres.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-1 receptor antagonism does not reduce the rewarding potency of cocaine in Swiss–Webster mice

Abstract: The orexin family of hypothalamic neuropeptides has been implicated in reinforcement mechanisms relevant to both food and drug reward. Previous behavioral studies with antagonists at the orexin A-selective receptor, OX1, have demonstrated its involvement in behavioral sensitization, conditioned place-preference, and self-administration of drugs of abuse. Adult male Swiss-Webster mice were implanted with stimulating electrodes to the lateral hypothalamus and trained to perform intracranial self-stimulation (ICS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
0
8
3
1
Order By: Relevance
“…Although this effect may be related to the unique pharmacodynamics of norBNI and other prototypical KOR antagonists (10), it may also indicate that there is redundancy in processes that modulate the activity of brain reward circuits or that phasic increases in orexin tone alone (unopposed by coreleased dynorphin) are insufficient to convey a reward signal from the stimulation site in the lateral hypothalamus. These findings may at first seem inconsistent with the work of others who examined SB334867 on ICSS threshold during the dark phase (21). However, there is considerable evidence that decreases in orexin function can have consequences that depend on whether animals are tested during their light or dark phase.…”
Section: Resultscontrasting
confidence: 63%
“…Although this effect may be related to the unique pharmacodynamics of norBNI and other prototypical KOR antagonists (10), it may also indicate that there is redundancy in processes that modulate the activity of brain reward circuits or that phasic increases in orexin tone alone (unopposed by coreleased dynorphin) are insufficient to convey a reward signal from the stimulation site in the lateral hypothalamus. These findings may at first seem inconsistent with the work of others who examined SB334867 on ICSS threshold during the dark phase (21). However, there is considerable evidence that decreases in orexin function can have consequences that depend on whether animals are tested during their light or dark phase.…”
Section: Resultscontrasting
confidence: 63%
“…In contrast, wild-type mice given an orexin 1 receptor antagonist and orexin knock-out mice display normal sensitization and locomotor response to morphine (Sharf et al, 2010). Also, orexin 1 receptor blockade fails to affect cocaine potentiation of brain stimulation-induced reward in mice (Riday et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, direct injection of OX-A into the ventral tegmental area is sufficient to reinstate an extinguished place preference (Tung et al, 2016). Further, cocaine-induced lowering of the intracranial self-stimulation threshold is also found to be reversed by systemic injection of SB-334867 in rats (Hollander et al, 2012), although this was not found to occur using a higher dose in mice (Riday et al, 2012). Overall, these results support a role for OX in the reward from cocaine intake.…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%